Development and Validation of the Online Interaction Scale in Organizational Context - Liu, Xin; Zhao, Chenhui; Chen, Zimeng; Wang, Qing (Frontiers in Psychology, 2022)
The evolution of Web 2.0 and social networks has led to the increased use of enterprise social media platforms (ESMP), making online interactions more common in organizations. However, few studies have researched online interactions in organizational context. This study addressed this gap using two research phases: a qualitative phase and a quantitative phase. The qualitative study phase identified two dimensions of online interaction: employee-employee online interaction and employee-platform online interaction. The employee-employee online interaction assessed responsiveness and suitability. The employee-platform online interaction assessed usefulness, applicability, and ease of use. The quantitative study phase applied a proposed conceptual framework derived from the qualitative study to create and validate measures for a new online interaction scale. This was done using a systematic scale development process. Measuring online interaction can help drive future quantitative research, providing an instrumental basis for further exploring the scientific management practice elements that govern employee psychology and behavior in cyberspace.